2017
DOI: 10.3389/fpls.2017.00772
|View full text |Cite
|
Sign up to set email alerts
|

A Dominant Negative OsKAT2 Mutant Delays Light-Induced Stomatal Opening and Improves Drought Tolerance without Yield Penalty in Rice

Abstract: Stomata are the main gateways for water and air transport between leaves and the environment. Inward-rectifying potassium channels regulate photo-induced stomatal opening. Rice contains three inward rectifying shaker-like potassium channel proteins, OsKAT1, OsKAT2, and OsKAT3. Among these, only OsKAT2 is specifically expressed in guard cells. Here, we investigated the functions of OsKAT2 in stomatal regulation using three dominant negative mutant proteins, OsKAT2(T235R), OsKAT2(T285A) and OsKAT2(T285D), which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…AtKC1 behaves as a general modulator of Shaker K in channels, reducing channel conductance and negatively shifting the activation threshold of these K in channels (Duby et al ., ; Wang et al ., , ; Jeanguenin et al ., ). In rice, the Shaker channel genes OsKAT2 and OsKAT3 are expressed in guard cells, and the silent OsKAT3 could interact with and negatively regulate OsKAT2 channel activity (Hwang et al ., ; Moon et al ., ). Therefore, these K in channels synergistically control stomatal opening, but the detailed mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 97%
“…AtKC1 behaves as a general modulator of Shaker K in channels, reducing channel conductance and negatively shifting the activation threshold of these K in channels (Duby et al ., ; Wang et al ., , ; Jeanguenin et al ., ). In rice, the Shaker channel genes OsKAT2 and OsKAT3 are expressed in guard cells, and the silent OsKAT3 could interact with and negatively regulate OsKAT2 channel activity (Hwang et al ., ; Moon et al ., ). Therefore, these K in channels synergistically control stomatal opening, but the detailed mechanisms are still unclear.…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, the Guard cell Outward-Rectifying K+ (GORK) channel, as a K+ efflux channel (K out ) in guard cells, induces stomatal closure [23,24]. The rice genome contains three OsKAT genes, OsKAT1, OsKAT2, and OsKAT3, which encode inward rectifying shaker-like potassium channels, and two OsAKTs (OsAKT1 and OsAKT2) [25,26]. Moon et al found that OsKAT2, a rice-KAT gene, is mainly expressed in guard cells involved in stomatal opening and was introduced as part of the response to drought stress [25].…”
Section: Introductionmentioning
confidence: 99%
“…The rice genome contains three OsKAT genes, OsKAT1, OsKAT2, and OsKAT3, which encode inward rectifying shaker-like potassium channels, and two OsAKTs (OsAKT1 and OsAKT2) [25,26]. Moon et al found that OsKAT2, a rice-KAT gene, is mainly expressed in guard cells involved in stomatal opening and was introduced as part of the response to drought stress [25]. It has also been stated that the OsKAT1 gene increases salinity tolerance in rice [26].…”
Section: Introductionmentioning
confidence: 99%
“…Stomatal movement therefore has crucial functions in the water usage efficiency of plants (Schroeder et al 2001). Thus far, the molecular mechanisms for stomatal closure and opening have been most studied in the model plant Arabidopsis, whereas studies in monocot plants, including most crops such as rice, maize, wheat and barley, have been limited (Chen et al 2017; Hwang et al 2013; Moon et al 2017; Raissig et al 2017; Sun et al 2016). In this study, we unraveled the core ABA signaling components and networks functioning in stomatal closure of rice, a model monocot plant.…”
Section: Discussionmentioning
confidence: 99%